Linguistic study of the names of works of art - Akhmedov Umid (Genius Journals, 2023)
This article tells about the linguistic and cultural characteristics of the symbolic lexemes in Russian and Uzbek languages, to explain the semantic and linguistic cultural processes in the formation of symbolic lexemes, to justify different approaches to the linguistic landscape of the world, the personal factor of changes in the semantics of words, socio-economic, analysis of the connection with psychological relations, identification of reality and lacunar units determines the relevance of that article.
Keywords: Lexemes; linguistics; grammatical